2017
DOI: 10.1038/s41598-017-08471-3
|View full text |Cite
|
Sign up to set email alerts
|

Mating-type genes of the anamorphic fungus Ulocladium botrytis affect both asexual sporulation and sexual reproduction

Abstract: Ulocladium was thought to be a strictly asexual genus of filamentous fungi. However, Ulocladium strains were shown to possess both MAT1-1-1 and MAT1-2-1 genes as observed in homothallic filamentous Ascomycetes. Here, we demonstrate that the U. botrytis MAT genes play essential roles for controlling asexual traits (conidial size and number). Using reciprocal genetic transformation, we demonstrate that MAT genes from the related heterothallic species Cochliobolus heterostrophus can also influence U. botrytis col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…It has been suggested that B. cinerea mating genes participate in processes other than mating because they remain transcriptionally active at different developmental stages of the fungus (59). The role of mating genes in fungal development, including hyphal growth, asexual sporulation, and pathogenicity, was previously reported for different filamentous fungi, including plant pathogens (63)(64)(65)(66)(67). Hence, even if this organism reproduces asexually, both mating types will still be maintained in a population.…”
Section: Discussionmentioning
confidence: 82%
“…It has been suggested that B. cinerea mating genes participate in processes other than mating because they remain transcriptionally active at different developmental stages of the fungus (59). The role of mating genes in fungal development, including hyphal growth, asexual sporulation, and pathogenicity, was previously reported for different filamentous fungi, including plant pathogens (63)(64)(65)(66)(67). Hence, even if this organism reproduces asexually, both mating types will still be maintained in a population.…”
Section: Discussionmentioning
confidence: 82%
“…In Penicillium chrysogenum, the MAT1-1-1 transcription factor also participates in key biological processes such as regulation of asexual development and morphogenesis, as well as amino acid, iron, and secondary metabolism (Becker et al 2015). The mating-type genes control conidial number and size in Ulocladium botrytis (Wang et al 2017). Virulence genes were also included among targets of mating-type transcription factors in Cryptococcus neoformans (Mead et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Though the teleomorph formation has never been successful, we found that the transcription levels of Ulocladium MAT1-1-1 and MAT1-2-1 genes were up-regulated on HAY culture media at 0-10 C with a light/dark cycle. MAT genes that are the key regulators for sexuality in filamentous ascomycetes are functional in Ulocladium (Geng et al, 2014;Wang et al, 2017), which could be activated by several environmental cues, and then control the sexual development in fungi. In addition, though specific environmental conditions can promote the expression of MAT genes of this genus, compared to Stemphylium botryosum, the significantly lower levels suggesting that environmental factors alone are insufficient to induce sexual progeny.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the majority of homothallic fungi, MAT1-1 and MAT1-2 idiomorphs are not closely linked and flanked by identical sequences in Ulocladium species. It has been reported that U. botrytis MAT genes have the ability to induce sexual recombination in Cochliobolus heterostrophus (Wang et al, 2017), indicating that MAT locus might be functional in Ulocladium, and the expression levels of MAT genes might directly affect sexual development in fungi. Thus, the Ulocladium species has the potential for sexual reproduction.…”
Section: Introductionmentioning
confidence: 99%